An integrated learning curriculum for radiography in South Africa - Engel-Hills, Penelope Claire (Cape Peninsula University of Technology, 2005)
The most significant changes and challenges to radiography in South Africa are rapid technological changes in the fields of imaging and radiation oncology, the changing status of radiographers as members of the multi-disciplinary health care team and the socioeconomic impact of post-apartheid ideology, policy and legislation with regard to both higher education and health provision. This altered landscape in which academic and clinical work is accomplished has impacted on radiography education. Curricula must change in order to equip graduates to work effectively in the modern workplace and the Integrated Learning Curriculum (ILC) is one such curriculum response. The traditional radiography curriculum of connecting subject-based theory education with interspersed clinical experience where there is reliance on students connecting or applying the subject content taught in the classroom to clinical practice was challenged. The ILC planned to enhance the integration of teaching, learning and assessment in the academy and workplace in a transforming South Africa. This study took advantage of the opportunity to capture data and learning from this curriculum renewal. The research was guided by the questions: I) What is the nature of radiographic knowledge? 2) What curricular options would facilitate radiographic knowledge? 3) What would enable or constrain successful curriculum implementation? 4) Is the ILC an appropriate curriculum for Radiography? This study facilitated a 'layered' understanding of integration and integrated curriculum through exploration of the concept 'integration'. This was achieved through; a national survey that investigated opinion on the status of radiography education in South Africa in 2003; interpretation of the context within which the ILC was located; a search of relevant literature; and a case study that gathered data over a three-year period. Findings support the notion that the workplace is a key influence on higher education curricula and that an integrated learning curriculum suits radiography.
Thesis (DTech (Radiography))--Cape Peninsula University of Technology, 2005.
Keywords: Radiography -- Curricula; Medicine -- Study and teaching -- South Africa; Radiography -- Study and teaching (Higher) -- South Africa.